Running-in Behavior in the Combination of Diamond-Like Carbon Film and AC8A Aluminum Alloy - Tomomi Honda (Japanese Society of Tribologists, 2018)
The running-in process affects the friction and wear properties of sliding materials in machines. If it is not done correctly, serious problems such as machine seizure may occur. Diamond-like carbon (DLC) films are used in various fields as an excellent tribo-material because of their low friction coefficient and high wear resistance. However, their running-in behavior has not been clarified quantitatively in detail. In addition, previous studies have not adequately investigated changes in wear particles during the running-in process. In the present work, we investigated the correlation between the friction coefficient and the number of wear particles during the runningin process using an online particle counter. Then, we compared the sliding distance at the completion of running-in judged using the particle counter with that judged using the friction coefficient. As a result, the running-in behavior in the combination of a DLC film and AC8A Al alloy is well clarified. In the case of a DLC/AC8A sliding pair, the DLC surface showed no significant changes after wear tests. The AC8A surface became smooth by abrasion and plastic deformation during running-in, and the ratio of silicon occupying the surface area increased slightly.